Sweat osmolarity shows intra‐animal regional variation in the horse. Issue 5 (30th June 2015) - Potts, Samantha; Thatcher, Rhys; Jones, Arwel W.; Warren, Lori K.; Tenbroeck, Saundra H.; Nottage, Florence; McEwan, Neil R.
<x xml:space="preserve">Abstract</x> Background Sweating is important in regulating body temperature but can be a source of loss of both fluids and electrolytes. Although the process has been studied in horses, the variation in sweat osmolarity across the body has not. Objectives This work describes an investigation to determine if there is regional variation in the osmolarity of sweat across different anatomical regions of the horse. Animals Ten horses were used in the study and were animals either stabled for riding lessons or had livery on‐site. Methods Sweat samples were collected from five regions on each horse following exercise and the osmolarity measurements were made using an Osmomat 030 (Gonotec, Berlin, Germany). Values were analysed by paired t‐tests and analysis of variance. Results Samples from the back and ears had statistically (P < 0.05) lower osmolarity values than those seen for the neck and forelimb, with thigh values intermediate between the other two sets of values. Conclusions and clinical importance Previous studies have used osmolarity values based on the sweat collected from the horse's back. The current work demonstrates that these values are probably an underestimation of electrolyte loss, which may have implications for the composition and administration of rehydration compounds.